2016
DOI: 10.3389/fphys.2016.00391
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Equivital EQ02 Lifemonitor with Holter Ambulatory ECG Device for Continuous Measurement of ECG, Heart Rate, and Heart Rate Variability: A Validation Study for Precision and Accuracy

Abstract: Background: The Equivital (EQ02) is a multi-parameter telemetric device offering both real-time and/or retrospective, synchronized monitoring of ECG, HR, and HRV, respiration, activity, and temperature. Unlike the Holter, which is the gold standard for continuous ECG measurement, EQO2 continuously monitors ECG via electrodes interwoven in the textile of a wearable belt.Objective: To compare EQ02 with the Holter for continuous home measurement of ECG, heart rate (HR), and heart rate variability (HRV).Methods: E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 27 publications
1
52
0
1
Order By: Relevance
“…17 Akintola et al (2016) used a chest wearable device detecting ECG and HRV and reported enormous amount of artifacts during daily activities in 18 healthy subjects and they concluded that this is a limitation of the wearable device used. 13 In agreement with all of the above, another study showed that the limits of agreement were deteriorating as the exercise was intensifi ed, implying an infl uence of adrenergic input, respiratory effort and unreliable algorithm detection and recording RR ability. 19 In contrast to the many negative results reported during intense exercise, there are other researchers who reported an overall stronger agreement.…”
Section: Exercisementioning
confidence: 66%
See 1 more Smart Citation
“…17 Akintola et al (2016) used a chest wearable device detecting ECG and HRV and reported enormous amount of artifacts during daily activities in 18 healthy subjects and they concluded that this is a limitation of the wearable device used. 13 In agreement with all of the above, another study showed that the limits of agreement were deteriorating as the exercise was intensifi ed, implying an infl uence of adrenergic input, respiratory effort and unreliable algorithm detection and recording RR ability. 19 In contrast to the many negative results reported during intense exercise, there are other researchers who reported an overall stronger agreement.…”
Section: Exercisementioning
confidence: 66%
“…11 Also, one study examined children. 12 In most of the articles (n=16), a chest device was used, [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] while a fi nger device was used in two studies 26,27 . Sixteen of the studies utilized a similar to ECG -HRV technology [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] and the remaining two integrated PPG -PRV technologies 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…Ambulatory HRV monitoring, however, appears to attracted increasing attention nowadays [9]. The long-term ambulatory measurement facilitates the track of HRV changes with activities of free living (e.g., exercise) [10].…”
Section: Introductionmentioning
confidence: 99%
“…When compared to other available systems, such as the Equivital LifeMonitor TM , the presented armband device offers the easy adaptability for individualized comfort. Though the Equivital offers accurate measurements of heart rate and heart rate variability via ECG, it is still susceptible to motion artifacts [29]. Proprietary software, Vivosense, can handle these artifacts, but at additional cost.…”
Section: Discussionmentioning
confidence: 99%